Antiseptic activity assay of ethanolic extract of Acehs rambutan rind (Nephelium lappaceum L.) against Staphylococcus aureus and its formulation as hand sanitizer gel - SARI, IRMA; FARADILLA, MEUTIA; PUTRI, RISKA ANANDA (Universitas Syiah Kuala, 2023)
The hands are one of the most susceptible parts of the human body to bacterial infection. One way to maintain health is to maintain hand hygiene. Ethanolic rambutan rind extract from Aceh province has been studied in order to determine if it can inhibit bacterial growth. This research was conducted to determine the antiseptic activity of the ethanol extract of rambutan rind against Stahpylococcus aureus by determining the phenol coefficient and determining whether the ethanolic extract of Acehs rambutan rind can be formulated into a hand sanitizer gel. Antiseptic activity testing was performed using the Rideal-Walker method which was carried out in 5 dilutions (1:100, 1:150, 1:200, 1:250 and 1:300). The absorbance measurement showed that the extract could act as an antiseptic, at a concentration of 1% and at a dilution of 1:200 which has phenol coefficient of 1.67. The ethanolic extract of Acehs rambutan rind can be formulated in the form of a hand sanitizer gel using 1% Carbopol as gelling agent. The results showed that the gel was brown with a distinctive menthol odor and changed into a dark brown color after a cycling test. The evaluation results of all formulas appropriated the requirements except for adhesion parameter. The results of the irritation test showed that the volunteers did not experience any signs of irritation. The results of the preference test showed that the respondents liked the shape and aroma parameters but not the color parameter.